Use of the 95-degree angled blade plate with biological and mechanical augmentation to treat proximal femur non-unions: a case series - Giovanni Vicenti; Giuseppe Solarino; Davide Bizzoca; Filippo Simone; Giuseppe Maccagnano; Giacomo Zavattini; Guglielmo Ottaviani; Massimiliano Carrozzo; Claudio Buono; Domenico Zaccari; Biagio Moretti (BMC Musculoskeletal Disorders, 2022)
Abstract Background Intertrochanteric and subtrochanteric non-union are rare but challenging complications. In the present study, we investigate the use of a 95° blade, in association with biological and mechanical augmentation, in the management of intertrochanteric and subtrochanteric femoral non-unions. Methods Between October 2015 and February 2021, a retrospective cohort study was conducted at our institution to investigate the use of a 95° blade, in association with biological and mechanical augmentation, in the management of intertrochanteric and subtrochanteric femoral non-unions, following the mechanical failure of the first device. All the patients underwent a clinical and radiographic follow-up at 6 weeks, 3, 6, 9, 12 and 18 months; at each follow-up, a plain radiograph of the femur was performed and patients were assessed using Harris Hip Score (HHS) and the Short Form-12 (SF-12) questionnaire. Results From October 2015 and February 2021, 40 proximal femur non-unions were managed at our Institution. Fifteen patients out of forty (37.5%) met the inclusion criteria. The main data of the study are summarized in Table 1; patients’ mean was 57 years old (range 19–83); 10 males and 5 females were included in the study. All the patients completely healed clinically and radiologically at an average of 6.1 months (range 4–13). All these patients returned to their pre-injury mobility status. During an average follow-up period of 25 months (range 8–60), the observed complications included wound dehiscence, which was treated with a superficial surgical debridement, a below-the-knee deep vein thrombosis, and a blade plate failure 3 months after the first revision surgery. Conclusions This study shows the treatment of inter-and sub-trochanteric non-unions with a 95° blade plate, medial strut allograft, and bone autograft obtained with RIA system, together with a varus malalignment correction, leads to a high percentage of bone healing, with a low incidence of complications and good clinical outcome.